Saluran Pemasaran Cabai Rawit di Kecamatan Puger Kabupaten Jember Provinsi Jawa Timur - FITRIYAH, ATIKATUL; ARTINI, NI WAYAN PUTU; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Marketing Channel for Cayenne Pepper in Puger Sub-District Jember Regency East Java Province The difference in the cayenne pepper marketing channels in Puger Sub-District, Jember Regency has an impact on the price for producers and consumers. The selling price of cayenne pepper at the farm level during the harvest season in July-September 2017 continues to decline and the bargaining position of farmers was considered weak. The purpose of this study was to find out the marketing institutions and channels, marketing functions, marketing efficiency (EP), and the ratio of the cost of cayenne pepper in Puger Sub-District. The data used were qualitative and quantitative data. The analysis used is descriptive qualitative and quantitative methods. The respondents of this study were 51 farmers (Mojosari, Grenden, and Jambearum Villages) which were determined by the proportional random sampling method and 15 marketing institution respondents determined by the snowball sampling method.The respondents of the marketing institutions consisted of one middleman, four sub-district level collecting traders, three inter-city traders, and seven retailers. There are three marketing channels namely, (1) farmers- collecting traders - retailers (Balung, Grenden, and Pasar Tanjung markets) - consumers, (2) farmers - collecting traders - inter-city traders (Jakarta) - markets in Jakarta, (3) farmers - middleman - collecting traders - inter-city traders (Jakarta) - markets in Jakarta. Every marketing institution performs marketing functions, namely exchange functions, physical functions, and facility functions. The functions performed by each institution are different. All marketing channels in this study are efficient. The most efficient marketing institution in the marketing channel I is the collecting traders,onmarketing channels II, namely inter-city traders, and on marketing channels III, namely inter-city traders with the same values as in marketing channels II. Each channel has a collecting trader. When it was compared, the collecting traders at channel I was the most efficient institution.